ANALISIS PINDAH PANAS PADA STERILISASI MINUMAN SUSU ULTRA HIGH TEMPERATURE (UHT) DI PT.ZYX - Reza Widyasaputra; Badrut Tamam; Novan Nandiwilastio; Citra Defira (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2021)
As perishable food, the sterilization process in milk was essential to obtain long shelf life. In industry, sterilization process was performed using high temperature in very short time. This process was known as Ultra High Temperature (UHT). UHT sterilization process could be done with Tubular Heat Exchanger (THE) or Plate Heat Exchanger (PHE). This research was aimed to compare the heat transfer rate from THE and PHE in PT.ZYX milk sterilization plant. Based on analysis, heat transfer rate of PHE was higher than THE. Both of them were using hot water as medium. The simulation with steam as heat transfer medium showed that the heat transfer rate was not much different with hot water in THE.